Analysis of influencing factors of multiple urethrocutaneous fistula after urethroplasty in children with hypospadias - Tian, Guangchao; Guo, Bingtao; Zhang, Lihua (Frontiers in Pediatrics, 2023)
Objective: To investigate the influencing factors of multiple UF(urethrocutaneous fistula) after urethroplasty in children with hypospadias. Methods: The clinical data of 195 children with UF after urethroplasty treated surgically in the Third Affiliated Hospital of Zhengzhou University from August 2015 to August 2022 were retrospectively analyzed and divided into single UF group (n=134) and multiple UF group (n=61) according to whether multiple UF occurred after urethroplasty. The possible correlated factors were collected and compared between the two groups, including hypospadias degree, length of formed urethra, time of urethroplasty, pre-urethroplasty weight, age at urethroplasty, urethroplasty style, season of urethroplasty , the first fistula repair method, season of the first fistula repair, diameter of the largest fistula of the first fistula repair, time of the first fistula repair surgery, and other 13 factors. Results: By univariate analysis, statistically significant differences were found between the two groups in age at urethroplasty, length of formed urethra, method of urinary drainage after urethroplasty, whether or not presence of purulent urethral drainage after first fistula repair, the first fistula repair method, and diameter of the largest fistula of the first fistula repair(P<0.05). After multifactorial analysis, the independent risk factors associated with multiple UF after urethroplasty were determined to be vesicostomy tube as urinary drainage method after urethroplasty(P<0.05,OR=6.574,95%CI: 2.720-15.891), presence of purulent urethral drainage after first fistula repair(P<0.05,OR=2.723,95%CI:1.214-6.109). Conclusions: Catheter as the drainage method after urethroplasty is an independent protective factor for multiple urethrocutaneous fistula, and the existing of purulent urethral secretions after the first fistula repair is an independent risk factor.